Micropropagation of the Halophyte Sarcocornia fruticosa (L.) A. J. Scott - Raposo, Maria Filomena de Jesus (2015)
Details of investigation to evaluate the effects of the number of nodes (one, two or three) of Sarcocornia fruticosa explants on growth and multiplication rate of plantlets are presented in this paper. The responses of the 3-node explants to some supplementary sources of different aminoacids and growth regulators indol-3-acetic acid, 6- benzylaminopurine and gibberellins A3 were also analysed. Plantlets from 3-node explants showed a marked increase in growth and number of lateral shoots, indicating that Sarcocornia does not respond well when explants are very small. The addition of 100 mg l-1 casein hydrolysate plus 150 mg l-1 glutamine, and 100 mg l-1 casein hydrolysate plus vitamins showed to be good growth promoters in micropropagating Sarcocornia, giving longer plantlets and higher multiplication rates